Strobilanthes Blume (Acanthaceae) in Myanmar, a new species and an updated checklist - John R. I. Wood; Mu Mu Aung; Tom Wells; Kate E. Armstrong (Kew Bulletin, 2022)
Summary A brief history of the discovery of Strobilanthes species in Myanmar is presented. The revival of fieldwork in recent years has resulted in many new records, so an updated checklist of all known species from the country is needed. Selected specimens are cited and distribution notes provided. One new species, Strobilanthes hians J.R.I.Wood & K.Armstr., with unusual pollen, is described and illustrated bringing the total of recognised species in the country to 81 with six additional infraspecific taxa.